Immunological evaluation of peptide vaccination for cancer patients with the HLA‐A26 allele. Issue 10 (25th September 2015) - Sakamoto, Shinjiro; Matsueda, Satoko; Takamori, Shinzo; Toh, Uhi; Noguchi, Masanori; Yutani, Shigeru; Yamada, Akira; Shichijo, Shigeki; Yamada, Teppei; Suekane, Shigetaka; Kawano, Kouichiro; Sasada, Tetsuro; et al.
Abstract : To develop a peptide vaccine for cancer patients with the HLA‐A26 allele, which is a minor population worldwide, we investigated the immunological responses of HLA‐A26 + /A26 + cancer patients to four different CTL epitope peptides under personalized peptide vaccine regimens. In personalized peptide vaccine regimens, two to four peptides showing positive peptide‐specific IgG responses in pre‐vaccination plasma were selected from the four peptide candidates applicable for HLA‐A26 + /A26 + cancer patients and administered s.c. Peptide‐specific CTL and IgG responses along with cytokine levels were measured before and after vaccination. Cell surface markers in PBMCs and plasma cytokine levels were also measured. In this study, 21 advanced cancer patients, including seven lung, three breast, two pancreas, and two colon cancer patients, were enrolled. Their HLA‐A26 genotypes were HLA‐A26:01 ( n  = 24), HLA‐A26:03 ( n  = 10), and HLA‐A26:02 ( n  = 8). One, 14, and 6 patients received two, three, and four peptides, respectively. Grade 1 or 2 skin reactions at the injection sites were observed in the majority of patients, but no severe adverse events related to the vaccination were observed. Peptide‐specific CTL responses were augmented in 39% or 22% of patients after one or two cycles of vaccination, respectively. Notably, peptide‐specific IgG were augmented in 63% or 100% of patients after one or two cycles of vaccination, respectively. Personalized peptide vaccines with these four CTL epitope peptides could be feasible for HLA‐A26 + advanced cancer patients because of their safety and higher rates of immunological responses. Abstract : Personalized peptide vaccine with 4 CTL epitope peptides could be feasible for HLA‐A26+ advanced cancer patients because of the safety and higher rates of immunological responses.